Sistem Prestasi Kehadiran Terintegrasi Finger Print Reader Pada Pt.Biru Semesta Abadi Berbasis Client Server - Fujiama Diapoldo Silalahi; Jarot Dian (Teknik: Jurnal Ilmu Teknik dan Informatika, 2021)
PT. Biru Semesata Abadi is a company engaged in refill drinking water, one of the many drinking water companies in Semarang, and has many branches (10 branches) and one head office in Semarang (in the Bugangan area, East Semarang district), because this company has franchise system. In this case, I will discuss the presence system (presence) of employees of PT. Biru Semesta Abadi, Fatmawati Semarang branch which is still manual (presence made of paper and written by hand) and still encounters many obstacles. This desire arises because this company has difficulties in processing Presence information data, resulting in more and more hardcopy archives and makes it difficult when the company management intends to recap and re-collect data and employee attendance lists. Presence Process that already exists in the Study of PT. Blue Semesta Abadi Semarang can be said that there are still shortcomings because everything is still done manuallyThe use of the Fingerprint method in this employee Presence system application will also make this Presence system more effective and efficient because each employee will only paste one of the employee's fingerprints on the available Fingerprint device where the calculation of the employee's attendance and exit hours will be entered in the database. , then the result of inputting the employee identification number will be the reference for the employee's arrival time.